Spectral indicators to detect the manifestations of desertification on farmland in Makhmour District - Hassan, Tarq Khidr (Zanco Journal of Human Sciences, 2021)
This study deals with the use of geographic information systems and remote sensing using spectral indicators to detect the manifestations of desertification on farmland in Makhmour District. The study aimed to investigate and monitor the indicators of desertification of agricultural lands in the study area using modern technologies in monitoring and evaluating the phenomenon of desertification and its effects on agricultural lands for a period of twenty-eight years by employing some indicators such as Normalized Difference Vegetation Index (NDVI), Normalize difference water index (NDWI) and Vegetation Moisture index(VMI) and Land Surface Temperature index (LST). The results of the study showed a deterioration of the deterioration of the vegetation cover, especially in the central and southern regions of the study, noting the spread of vegetation and agricultural cover in 1998, and decreased vegetation and agricultural cover gradually in the rest of the years and in 2016 we find that the vegetation and agriculture in The study also contributed to the creation of a database and maps on the state of desertification and its extension. In m Clunk study for four different periods (1988, 1998,2008,2016).